ICT's wide web: a system-level analysis of ICT's industrial diffusion with algorithmic links - Ekaterina Prytkova (Friedrich Schiller University Jena, 2021)
This paper seeks to contribute to the understanding of diffusion patterns and relatedness withinICT as a technology system in the EU28 region. Considering ICT as a technology system, first,I break down ICT into a set of distinct technologies employing OECD and WIPO classifications.Then, using text analysis and the Algorithmic Links with Probabilities method, I construct industry-technology links to connect industries with ICT and track ICT's diffusion over the period 1977-2020.The analysis highlights the heterogeneity of the technologies that constitute the ICT cluster. Asnot all ICTs are pervasive and not all ICTs are key technologies, this leads to differences in industryreliance on them. The results indicate that the ICT cluster shows signs of a "phase transition",passing the phase of building bulk elements of the infrastructure and around the 2000s entering thephase of working on the functionality for business applications deployment and users' convenience.This transition is marked by the surging relevance of ICT technologies such as mobile communication,information analysis, security, and human interface. Studying the ICT as a cluster allows puttingeach ICT technology in context to compare them in relative terms; this is especially important forthe discussion of novel and fast-growing technologies such as Artificial Intelligence (AI). Concerningthe structure of industry reliance on the ICT cluster, ICT's penetration is characterized by increasingscope but unevenly distributed scale; depending on the industry and the distinct ICT technologythe intensity of their connections varies significantly. Remarkably, looking closer at AI technologies,in line with the current literature, a wide array of "shallow" connections with industries is revealed.Finally, I calculate relatedness metrics to estimate proximity among ICT technologies. The analysisreveals differences in the underlying knowledge base among the overwhelming majority of the ICTtechnologies but a similar structure of their application base.
Keywords: O33; O52; O14; 330; ICT; algorithmic links; artificial intelligence; relatedness; industry-technology nexus